Psychological Anthropology: A Critical Review of the Book Culture and Identity - Asghar Izadi-Jeiran (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The relationship between individual and culture as the main subject in psychological anthropology had been engaged anthropologists from the early days of the discipline. Culture and Identity: The History, Theory, and Practice of Psychological Anthropology (second edition, 2007) by Charles Lindholm is one of the best and most comprehensive resources in this field. The book is organized into five sections, with thirteen chapters. Lindholm began the book by exploring of self and individual in the culture and thought of the West, then turn to anthropology to show its contribution through ethnographic research. Some classic subjects of psychology such as self, thinking, emotions, and mental disorders are discussed by reference to anthropological legacy. Culture and Identity has many strengths including a good and concise review of philosophical approaches, extensive use of data of anthropological fieldworks, grounding the discussions of psychological anthropology in the broader contexts of some events in the scientific community, comprehensiveness of bibliography, and combining theory with experimental examples.